Clinical Manifestation and Short-Term Outcome of Emergency Percutaneous Revascularization of Patient with ST-Segment Elevation Myocardial Infarction at a Rural Satellite Center - Sarfraz Hussain Sahito, Muhammad Rafique Kanher, Javed Khurshed Shaikh, Tariq Ashraf, Rizwan Khan, Amjad Ali Hulio (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In Pakistan, the prevalence of acute coronary syndrome (ACS) patients is among the highest in the world. A patient’s rate of morbidity and mortality depends greatly on the time that passes during ACS, especially in ST-elevation myocardial infarction patients (STEMI). Objectives: This research aimed to assess the spectrum of the acute coronary syndrome (ACS) and factors leading to delay in presentation and treatment to evaluate its impact on the short-term outcome in patients presenting to a rural satellite center of NICVD at Khairpur, Pakistan. Material & Methods: This observational study was conducted on 400 patients at the Department of Adult Cardiology at Kharipur Satellite Center of National Institute of Cardiovascular Diseases (NICVD), Pakistan for six months. All patients presenting to ER with ACS whose age was ≥18 years were included. Participants’ informed consents were obtained verbally and confidentiality was maintained in regards to their participation in and publication of findings from the study. Consecutive patients presenting with ACS to the satellite center of NICVD at Khairpur, Pakistan were included in this research. Baseline characteristics were analyzed using the statistical package for social sciences (SPSS 25). Results: A total of 400 (295 males and 105 females) patients with ACS were included. The mean age was 63.3 ± 11.5 (range 40-70) years, 42.5% had low SES, 35.0% had mid-SES, and 22.5% had high SES.159 (39.8%) patients were from the urban area and 241(60.2%) were from a rural region. However, age, smokers, hypertension, dyslipidemia, area of residence, obesity, diabetic Mellitus, and atrial fibrillation were found to be significant factors associated with socioeconomic status for the acute coronary syndrome. (p-value = <0.05) The epicardial coronary disease was significantly less common in individuals with a high SES compared to those with a mid or low SES. We observed that mode of transport may be a significant cause of death (p-value = <0.0001) because of late arrival to the hospital. In our research, we showed 7.8% 30-day mortality out of total samples. Area of residence, mode of transport, 30-day mortality, OS-ECG (in min), and inferior and anterior STEMI were found to be significantly associated factors (p-value = <0.05). Conclusion: Even though the low-SES STEMI patients at the National Institute of Cardiovascular Diseases Khairpur show more adverse clinical and cardiovascular risk factors than patients from urban areas with higher SES. The 30-day mortality for these patients is comparable to the higher-SES patients.